Molecular mechanisms, off‐target activities, and clinical potentials of genome editing systems - Nannan Zheng; Liyang Li; Xiangdong Wang (Clinical and Translational Medicine, 2020)
Abstract Methodologies of genome editing are rapidly developing with the improvement of gene science and technology, mechanism‐based understanding, and urgent needs. In addition to the specificity and efficiency of on‐target sites, one of the most important issues is to find and avoid off‐targets before clinical application of gene editing as a therapy. Various algorithms, modified nucleases, and delivery vectors are developed to localize and minimize off‐target sites. The present review aimed to clarify off‐targets of various genome editing and explore potentials of clinical application by understanding structures, mechanisms, clinical applications, and off‐target activities of genome editing systems, including CRISPR/Cas9, CRISPR/Cas12a, zinc finger nucleases, transcription activator‐like effector nucleases, meganucleases, and recent developments. Current genome editing in cancer therapy mainly targeted immune systems in tumor microenvironment by ex vivo modification of the immune cells in phases I/II of clinical trials. We believe that genome editing will be the critical part of clinical precision medicine strategy and multidisciplinary therapy strategy by integrating gene sequencing, clinical transomics, and single cell biomedicine. There is an urgent need to develop on/off‐target‐specific biomarkers to monitor the efficacy and side‐effects of gene therapy. Thus, the genome editing will be an alternative of clinical therapies for cancer with the rapid development of methodology and an important part of clinical precision medicine strategy.